The roots of Texas music - Clayton, Lawrence, 1938-2000.; Specht, Joe W., 1945- (College Station : Texas A & M University Press, 2003)
Contains nine essays in which the authors examine various aspects of Texas music from its beginnings to 1950, providing an overview of Texas music history, and discussing Texan jazz, country music, early Texas bluesmen, classical and religious music, and various ethnic genres.
The roots run deep : an overview of Texas music history / by Gary Hartman -- Texan jazz, 1920-50 / Dave Oliphant -- Put a nickel in the jukebox : the Texas tradition in country music, 1922-50 / Joe W. Specht -- Early Texas bluesmen / John Lightfoot -- Roots of classical music in Texas : the German contribution / Larry Wolz -- Make a joyful noise : some popular religious music in twentieth-century Texas / Kenneth W. Davis -- Chicano music : evolution and politics to 1950 / José Angel Gutiérrez -- Czech and Polish music in Texas before World War II / Carolyn F. Griffith -- Black Creoles and the evolution of zydeco in southeast Texas : the beginnings to 1950 / Roger Wood.
Includes index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Includes bibliographical references and index.
Keywords: Music -- Texas -- History and criticism; Musique -- Texas -- Histoire et critique; MUSIC -- History & Criticism; Music; Texas; Musik; Texas; Criticism, interpretation, etc